Does body mass index (BMI) influence the Ankylosing Spondylitis Disease Activity Score in axial spondyloarthritis? - Robert Landewé; Désirée van der Heijde; Hanne Dagfinrud; Roberta Ramonda; Floris A van Gaalen; Rosaline van den Berg; Pauline A C Bakker; Zineb Ez-Zaitouni; Miranda van Lunteren; Esmeralda Molenaar; Roxana Rubio Vargas (RMD Open)
Objective Obesity is associated with elevated C reactive protein (CRP) levels. The Ankylosing Spondylitis Disease Activity Score (ASDAS) combines patient-reported outcomes (PROs) and CRP. We evaluated the effect of body mass index (BMI) on CRP and on ASDAS, and studied if ASDAS can be used in obese axial spondyloarthritis (axSpA) patients to assess disease activity.Methods Baseline data of patients with chronic back pain of short duration included in the SPondyloArthritis Caught Early (SPACE) cohort were used. Collected data included BMI and ASDAS. Patients were classified according to the ASAS axSpA classification criteria and BMI (overweight ≥25 and obese ≥30). Correlation and linear regression analyses were performed to assess the relation between BMI and ASDAS. Linear regression models were performed to assess if age or gender were effect modifiers in the relation between BMI and CRP, and between BMI and ASDAS.Results In total, 428 patients were analysed (n=168 axSpA; n=260 no-axSpA). The mean age was 31.1 years, 36.9% were male, 26.4% were overweight and 13.3% obese, median CRP was 3 mg/L and the mean ASDAS was 2.6. Gender was the only factor modifying the relationship between BMI and CRP as BMI had an influence on CRP only in females (β=0.35; p<0.001). Correlations between BMI and CRP or PROs were generally weak, and only significant for CRP in female patients. BMI was not related to ASDAS in axSpA patients.Conclusions ASDAS is not affected by BMI in axSpA patients. Therefore, based on our data it is not necessary to take BMI in consideration when assessing disease activity using ASDAS in axSpA patients.